2020
DOI: 10.5155/eurjchem.11.4.351-363.2043
|View full text |Cite
|
Sign up to set email alerts
|

Mitigate the cytokine storm due to the severe COVID-19: A computational investigation of possible allosteric inhibitory actions on IL-6R and IL-1R using selected phytochemicals

Abstract: The novel corona virus 2019 (COVID 19) is growing at an increasing rate with high mortality. Meanwhile, the cytokine storm is the most dangerous and potentially life-threatening event related to COVID 19. Phyto-compounds found in existing Ayurveda drugs have the ability to inhibit the Interleukin 6 (IL-6R) and Interleukin 1 (IL-1R) receptors. IL-6R and IL-1R receptors involve in cytokine storm and recognition of phytochemicals with proven safety profiles could open a pathway to the development of the most effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 73 publications
(72 reference statements)
0
3
0
Order By: Relevance
“…The results of this study showed that AMI patients infected with COVID-19 had a signi cantly increased risk of thrombosis compared with AMI patients not infected with COVID-19. SARS-CoV-2 infection can lead to the release of a large number of in ammatory cytokines, such as interleukin-6, interleukin-8 and tumor necrosis factor, which can reduce the activity of the micro-vessels, thereby affecting microcirculatory hemodynamics and promoting thrombosis [22][23][24]. In addition, the SARS-CoV-2 virus invades the organism and binds to the ACE-2 receptor, which activates the renin-angiotensin system, leading to an increase in Angiotensin II, vasoconstriction, and damage to the vascular endothelium, thus causing platelet aggregation.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study showed that AMI patients infected with COVID-19 had a signi cantly increased risk of thrombosis compared with AMI patients not infected with COVID-19. SARS-CoV-2 infection can lead to the release of a large number of in ammatory cytokines, such as interleukin-6, interleukin-8 and tumor necrosis factor, which can reduce the activity of the micro-vessels, thereby affecting microcirculatory hemodynamics and promoting thrombosis [22][23][24]. In addition, the SARS-CoV-2 virus invades the organism and binds to the ACE-2 receptor, which activates the renin-angiotensin system, leading to an increase in Angiotensin II, vasoconstriction, and damage to the vascular endothelium, thus causing platelet aggregation.…”
Section: Discussionmentioning
confidence: 99%
“…The four structures studied in molecular docking were submitted to the later stage of the study using the methodological approach of Rajapaksha et al, (2020) Yang et al, (2020) and Oso et al, (2020).…”
Section: Molecular Dynamicsmentioning
confidence: 99%
“…al. showed that the phytochemicals (taepeenin J and Nortaepeenin B) found in existing Ayurveda drugs have the ability to inhibit the Interleukin 6 (IL-6R) and Interleukin 1 (IL-1R) receptors and are the potential candidates for further in vitro studies for the development of medicine against cytokine storm on behalf of SARS-COV-2 infected patients. The study was proved through computational investigation of possible allosteric inhibitory actions on IL-6R and IL-1R using selected phytochemicals [110].…”
Section: Types Of Vaccinesmentioning
confidence: 99%